Effect of different aging treatments on the vigor of high-oleic acid peanut seeds. (October 2019) - Wang, H; Yu, S T; Wang, C T; Yu, G Q; Cui, X Y; You, S L; Gao, Z Y; Shi, P X; Yu, H B; Ren, L
Abstract: Accelerated aging is known to reduce seed viability and vigor in many crop species. This study was undertaken to evaluate the effect of accelerated aging on germination potential, germination percentage, electric conductivity, acid value and peroxide value. Compared with common peanut, high oleic acid peanut were more beneficial to health and can significantly improve the storability of seed. Eight high oleic acid (range of oleic acid content: 74.95%-80.6%) and two common varieties were used in this experiment. Six treatments were contained, natural aging of kernels, natural ageing of pods, accelerated aging was achieved by incubating seed at 40°C and 100% relative humidity in a closed chamber for 4, 6, and 8 days. The results showed that: the changes of germination potential and germination percentage of natural aging were not significant for high oleic acid peanuts, smaller than that of the common varieties. No matter artificial aging or natural aging treatment, compared with non-aging treatment, electric conductivity gradually increased, but high oleic acid varieties remained at low levels. The acid value of each variety increased gradually with the aging time, comparison between aging treatments, the difference between high oleic acid varieties was not significant, not the same with the common varieties. The peroxide value of 8 high oleic acid varieties was zero under each aging treatment, but the peroxide value of two common varieties increased with the aging time. The variation rules of all indicators of artificial aging for 4 days and 6 days were the same with the two natural aging treatments. So artificial aging for 4 days and 6 days can be used for high oleic acid aging test, replace natural aging, which not only shortens the test time but also ensuring the best effect.